Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Review: 32

Answer

2P(x)-Q(x)=-$x^{2}$+2x+3

Work Step by Step

P(x)=2x-1 Q(x)=$x^{2}$+2x-5 2P(x)-Q(x)=2(2x-1) -($x^{2}$+2x-5) 2P(x)-Q(x)=4x-2-$x^{2}$-2x+5 2P(x)-Q(x)=-$x^{2}$+2x+3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.